Skeletonema costatum of mangrove ecosystem: Its dynamics across physico-chemical parameters variability - Redzuan, Nurul Shahida; Milow, Pozi (Bioflux SRL, 2019)
As part of a monitoring programme, twelve months total phytoplankton sampling were carried out starting from April 2009 to March 2010 in Carey Island mangrove ecosystem across measured physico-chemical and total phytoplankton diversity parameters. Across the one year sampling period, we found three major occurrences of mono-species bloom of Skeletonema costatum in the month of April, May and August 2009, in which the water body at study site displayed dark brown colour. This diatom species that displayed significant temporal variation has been found to grow rapidly when the nitrate concentration and temperature of the water column were > 0.6 mg L -1 and > 31°C, respectively. This study shows that S. costatum displayed negative correlation with dissolved oxygen in the water column. Increase in S. costatum cells abundance at the study site proved to destabilize total phytoplankton diversity by decreasing the equitability (measured by evenness) of total phytoplankton. © 2019, BIOFLUX SRL. All rights reserved.